Introduction: (De) Fatalizing the Present - Agathangelou, Anna M. (InTensions, 2011)
This special issue, (De) Fatalizing the Present and Creating Radical Alternatives, brings critical theorists, artists, and poets together to engage systematically the temporal structure of the relationship of politics and violence with a focus on the tensions between slavery and colonization. These theorists show that disrupting dominant theorizations and their generated contingent affects begins with exposing the epistemologies and methods that call for a monitoring of each other’s activities in the aggregate without taking into account the current politico-ontologico-structural condition of world politics, inscribing the slave condition as a primary one, while also continually and constantly changing. This special issue expands the postcolonial critique that challenges the idea of the “West” and the “Global North” as primary analytical sites and their citizens the agents of politics against which everybody else is to be measured. Such critiques open up the space for us to take time as the primary object of focus in our analyses of the global, problems in world politics, ethics, and possible expressions of revolutionary practices.